Pemanfaatan Geopolimer Abu Terbang Sebagai Pozzolanic Tanah Lempung Untuk Material Tanah Dasar Perkerasan - Soewignjo Agus Nugroho; Puspa Ningrum; Muhardi Muhardi (JURUSAN TEKNIK SIPIL, 2020)
California Bearing Ratio (CBR) is one of a method for determining soil bearing capacity. Extraction of industrial disposal to be used as material for road pavement construction is still lacking. This research aims to determine changing CBR values due to the fly ash addition in clay under conditions with or without curing and soaked. Samples curing for 28 days were done in two conditions firstly, curing in mold and wrapped with plastic. Secondly, wrapped with plastic off mold. Looking at the CBR test results, plasticity index, density and specific gravity (Gs) is decreased. The addition of fly ash rises the value of the optimum water content (OMC). CBR value increased due to the addition of fly ash, a significantly increase occurred in the fly ash addition by 15%. Curing method uses different CBR values, where curing using mold has a high CBR value. In soaked CBR test, the CBR value varies due to the characteristics of the fly ash and clay which absorbed water. Water absorption varies depend on the percentage of the mixture of fly ash content and clay. The width variance of moisture content with OMC, because water absorption, affect to value of CBR. Samples with moisture content is more close to OMC the CBR value is more bigger